2024
DOI: 10.1200/cci.23.00046
|View full text |Cite
|
Sign up to set email alerts
|

Raising the Bar for Real-World Data in Oncology: Approaches to Quality Across Multiple Dimensions

Emily H. Castellanos,
Brett K. Wittmershaus,
Sheenu Chandwani

Abstract: PURPOSE Electronic health record (EHR)–based real-world data (RWD) are integral to oncology research, and understanding fitness for use is critical for data users. Complexity of data sources and curation methods necessitate transparency into how quality is approached. We describe the application of data quality dimensions in curating EHR-derived oncology RWD. METHODS A targeted review was conducted to summarize data quality dimensions in frameworks published by the European Medicines Agency, The National Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In an exploration of the DQ literature, we found 10 other reviews that summarise the most frequently represented DQ dimensions across DQ studies, software, and theoretical frameworks [19,21,[23][24][25][26][27][28][29][30]. All 10 reviews demonstrated the concept of completeness to be well represented.…”
Section: Data Quality Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In an exploration of the DQ literature, we found 10 other reviews that summarise the most frequently represented DQ dimensions across DQ studies, software, and theoretical frameworks [19,21,[23][24][25][26][27][28][29][30]. All 10 reviews demonstrated the concept of completeness to be well represented.…”
Section: Data Quality Theorymentioning
confidence: 99%
“…The need for high-quality data was exemplified during the COVID-19 pandemic, when EHR-RWD was critical for research and planning [15]. Regulatory authorities, such as the FDA (Food and Drug Administration), EMA (European Medicines Agency), NICE (National Institute for Health and Care Excellence), and MHRA (Medicines and Healthcare products Regulatory Agency), recommend the reporting of DQ metrics and dimensions to provide additional context to real-world study outcomes, therefore serving as the foundation for trustworthy RWE [3,14,[16][17][18][19]. These guidelines mostly promote ad-hoc DQ assessment and reporting, with the exception that EMA briefly notes the importance of assessing DQ as close as possible to the moment of data capture to help with collection errors [3,[16][17][18].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…25 The need for transparency was emphasized in an editorial written by the FDA and published in this journal. 26 In the same issue, an assessment of DQ in one oncology RWD source provides insight into the challenges in creating a fitfor-purpose oncology RWD source. 27 The evolving consensus among stakeholders appears to agree on the following elements required to produce credible RWE from nonrandomized noninterventional studies.…”
Section: Challenges To the Uptake Of Rwd And Rwementioning
confidence: 99%
“…Audit trails starting at data extraction and extending through maintenance and retention that include access to source records or certified copies can help promote transparency and reproducibility. The analysis by Castellanos et al 4 highlights the importance of transparency as a means to characterize fitness-for-use of a singular specific RWD source. However, this high-level assessment of fitness-for-use is limited absent a specific research question.…”
mentioning
confidence: 99%
“…In addition, pragmatic trials may incorporate RWD to minimize clinician and patient burden and streamline design while maintaining randomization, with the potential to generate evidence for new indications and evaluate safety and effectiveness in the postmarketing setting. 16 Finally, as alluded to by Castellanos et al, 4 a vast amount of unstructured RWD for oncology are becoming available including radiology reports, laboratory reports, physician notes, and genomic sequencing data. Whereas manual abstraction of such data is labor intensive, the application of artificial intelligence (AI), including techniques such as natural language processing, large language models, and machine learning, holds promise as a means to facilitate data abstraction.…”
mentioning
confidence: 99%